Foreign and Intratrade Policies of Arab Countries - El-Naggar, Said (International Monetary Fund, 1992)
The challenge facing the Arab countries to maintain economic growth in the face of the deteriorating terms of trade affecting all developing countries was addressed in a seminar held in Abu Dhabi in early 1992. This volume, edited by Said El-Naggar, includes papers by contributors from the region as well as from the IMF.